2014
DOI: 10.1002/rcm.6884
|View full text |Cite
|
Sign up to set email alerts
|

Probing the exposure of the phosphate group in modified amino acids and peptides by ion-molecule reactions with triethoxyborane in Fourier transform ion cyclotron resonance mass spectrometry

Abstract: The ability of a phosphorylated species to react with TEB depends on the ease of access to the phosphate moiety in the corresponding gaseous ion. Measuring the kinetic efficiency of such reactions can represent a valuable tool to explore the accessibility of phosphate groups in biomolecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Studies by Kenttämaa and coworkers (Duan et al, 2008(Duan et al, , 2009Eismin et al, 2012;Habicht et al, 2008;Sheng et al, 2015Sheng et al, , 2016Somuramasami et al, 2010;Yerabolu et al, 2017;Zhu et al, 2016Zhu et al, , 2017 on the identification of specific functional groups in organic analytes and their mixtures have progressed to combination of IMR with separation techniques as well as to the development of an advanced multi-pulsed-valve for introducing neutral reagents into the instrument vacuum system. Similarly, IMR play an important role in structure identification of radical ions of peptides (Lanucara et al, 2014;Piatkivskyi, Piatkivskyi, Hurt, et al, 2014;Piatkivskyi, Piatkivskyi, Ryzhov, et al, 2014), especially since ion dissociation methods are often hampered by the facile radical rearrangement. Lastly, a novel radical-based dissociation method, HAD has been recently developed by Takahashi and coworkers (Asakawa et al, 2018a(Asakawa et al, , 2018bAsakawa et al, 2020aAsakawa et al, , 2020bAsakawa et al, 2019aAsakawa et al, , 2019bAsakawa et al, 2019;Shimabukuro et al, 2018;Takahashi et al, 2016;Takahashi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Kenttämaa and coworkers (Duan et al, 2008(Duan et al, , 2009Eismin et al, 2012;Habicht et al, 2008;Sheng et al, 2015Sheng et al, , 2016Somuramasami et al, 2010;Yerabolu et al, 2017;Zhu et al, 2016Zhu et al, , 2017 on the identification of specific functional groups in organic analytes and their mixtures have progressed to combination of IMR with separation techniques as well as to the development of an advanced multi-pulsed-valve for introducing neutral reagents into the instrument vacuum system. Similarly, IMR play an important role in structure identification of radical ions of peptides (Lanucara et al, 2014;Piatkivskyi, Piatkivskyi, Hurt, et al, 2014;Piatkivskyi, Piatkivskyi, Ryzhov, et al, 2014), especially since ion dissociation methods are often hampered by the facile radical rearrangement. Lastly, a novel radical-based dissociation method, HAD has been recently developed by Takahashi and coworkers (Asakawa et al, 2018a(Asakawa et al, , 2018bAsakawa et al, 2020aAsakawa et al, , 2020bAsakawa et al, 2019aAsakawa et al, , 2019bAsakawa et al, 2019;Shimabukuro et al, 2018;Takahashi et al, 2016;Takahashi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Lanucara et al (2014) used a similar approach to probe exposure of the phosphate group in modified amino acids and peptides by IMR with triethoxyborane in FT‐ICR MS. They concluded that measuring the kinetics of such reactions can represent a valuable tool to explore the accessibility of phosphate groups in biomolecules.…”
Section: Functional‐group‐specific Imrmentioning
confidence: 99%
“…Furthermore, an rf‐only quadrupole functions as a focusing reaction chamber and hence has a great ion transmission capability. However, the most powerful instruments for the study of these reactions are ion‐trapping instruments, such as Fourier‐transform ion cyclotron resonance (FT‐ICR) (Gao et al, 2003; Lanucara et al, 2014; Petzold et al, 2004; Watkins et al, 2004), linear quadrupole ion trap (LQIT) (Habicht et al, 2008, Habicht, Duan et al, 2011; Kong et al, 2018; Sheng, Williams, Tang, Riedeman et al, 2014) and three‐dimensional quadrupole ion trap (QIT) instruments (Piatkivskyi, Pyatkivskyy, Hurt, et al, 2014; Piatkivskyi, Pyatkivskyy, Ryzhov, 2014; Pyatkivskyy & Ryzhov, 2008; Song & Cooks, 2006). These instruments enable the execution of multiple stages of ion isolation followed by ion‐molecule reactions or dissociation reactions (MS n experiments), thus providing great flexibility and the ability to probe the structures of the ion‐molecule reaction product ions.…”
Section: Instrumental Aspectsmentioning
confidence: 99%